2017
DOI: 10.2196/jmir.9266
|View full text |Cite
|
Sign up to set email alerts
|

Using Social Media Data to Understand the Impact of Promotional Information on Laypeople’s Discussions: A Case Study of Lynch Syndrome

Abstract: BackgroundSocial media is being used by various stakeholders among pharmaceutical companies, government agencies, health care organizations, professionals, and news media as a way of engaging audiences to raise disease awareness and ultimately to improve public health. Nevertheless, it is unclear what effects this health information has on laypeople.ObjectiveThis study aimed to provide a detailed examination of how promotional health information related to Lynch syndrome impacts laypeople’s discussions on a so… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 35 publications
2
25
0
Order By: Relevance
“…For RQ2, we found that 87 consumer topics (out of 122) are correlated with promotional information, suggesting that promotional health information on Twitter certainly has an impact on consumers' discussions, which is consistent with our previous study on Lynch syndrome [22].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…For RQ2, we found that 87 consumer topics (out of 122) are correlated with promotional information, suggesting that promotional health information on Twitter certainly has an impact on consumers' discussions, which is consistent with our previous study on Lynch syndrome [22].…”
Section: Discussionsupporting
confidence: 90%
“…We then categorized these tweets into either: (1) promotional information, or (2) consumers' discussions. Consistent with our previous findings [22], tweets that contain URLs are more likely to be promotional information, where the URLs are links to HPV-related news, research findings, and health promotion activities. We randomly annotated 100 tweets with URLs and found 95% are promotioinal information.…”
Section: Step 2: Rule-based Categorization Of the Tweetssupporting
confidence: 89%
“…Preliminary results show that the best filters are based on the number of related posts a user sends. The profiling of Twitter's users to enhance tweet classification and relevance was already proposed as an open issue in [19].…”
Section: Using Social Network For Phsmentioning
confidence: 99%
“…Text classification is a common task in natural language processing (NLP) and a building block for many complex NLP tasks. Text classification is the task of classifying an entire text by assigning it one or more predefined labels [1] with broad applications in the biomedical domain, including biomedical literature indexing [2,3], automatic diagnosis codes assignment [4,5], tweets classification for public health topics [6][7][8], patient safety reports classification [9], etc.…”
Section: Introductionmentioning
confidence: 99%